(untitled) (Global Journal of Human-Social Science, 2014)
This paper makes an attempt to understand women’s position under the society and the way it has affected our globalised society. The present paper is an attempt to study the status of women empowerment and development in India using various indicators like women’s inspiration in household decision making power, financial autonomy, political participation, freedom of movement, acceptance of unequal gender role, exposure to media, access to education, experience of domestic violence etc. In recent years, the emphasis has included empowerment, which increases women’s decision-making capability and well-being. It analyses the strategies that Women Education and Inspiration has used to mobilize and empower selfemployed. Inspiration and Education is the most powerful tool of change of position in our globalized society. The focal point of this paper may be treated as one directly related with development studies. The social understanding of the empowerment and development of women in India must be treated as an unfinished and continuing process.